1995
DOI: 10.1007/bf02260439
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of water sources and other determinants to prevalence of intestinal protozoal infections in a rural community of Saudi Arabia

Abstract: A study was carried out in a rural area of Asir region in Southwest of Saudi Arabia where information on the types of domestic water supply and sociodemography in relation to intestinal protozoal infections were obtained from 1417 inhabitants (81.4% of the total) of nine villages. Stool samples were collected from the study population and examined for intestinal parasites. Overall, the prevalence rates of infection with the common water-borne parasites, Giardia lamblia and Entamoeba histolytica were 18.9% and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 7 publications
0
13
1
1
Order By: Relevance
“…Hoque et al [33] found a significant odds ratio of 8.3 for people that consumed roof harvested rainwater compared to those consuming water from the main water supply network of Auckland. Omar et al [40] also found a significant odds ratio of 2.97 for giardiasis in people that consumed rainwater, rather than desalinated water.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Hoque et al [33] found a significant odds ratio of 8.3 for people that consumed roof harvested rainwater compared to those consuming water from the main water supply network of Auckland. Omar et al [40] also found a significant odds ratio of 2.97 for giardiasis in people that consumed rainwater, rather than desalinated water.…”
Section: Discussionmentioning
confidence: 96%
“…As reported in the literature, the correlation between water consumption and pathogenic protozoa, especially G. duodenalis , infections has been demonstrated [2], [40]. However, the question of what sources of water supply increase the risks of infection by these protozoa is still controversial because they have been detected in surface and underground sources and in rainwater.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, the using of well water has been identified as significant predictors of E. histolytica and Giardia infections in Saudi Arabia. Comparatively, those who use desalinated water have the lowest degree of exposure to the risk of infection 25 . Faecal matter and their offensive odour are also common sight and perception around some water sources.…”
Section: Discussionmentioning
confidence: 99%
“…Authors attributed the increased prevalence recorded at the same locality (Jeddah) from 2007 (8.3%) to 2010 (20%) to the type of domestic water used because most cases diagnosed with higher rates drank water from wells designated for drinking water or from home tanks used for other purposes. However, patients who used desalinated water for these purposes were reported to have the lowest degree of exposure to amebiasis (Omar et al, 1995).…”
Section: Global Distributionmentioning
confidence: 99%